Bidirectional regulation between TMEFF2 and STAT3 may contribute to Helicobacter pylori‐associated gastric carcinogenesis. Issue 5 (7th July 2014) - Sun, Tian‐Tian; Tang, Jia‐Yin; Du, Wan; Zhao, Hui‐Jun; Zhao, Gang; Yang, Sheng‐Li; Chen, Hao‐Yan; Hong, Jie; Fang, Jing‐Yuan
<x xml:space="preserve">Abstract</x> The transmembrane protein with epidermal growth factor and two follistatin motifs 2 (TMEFF2) is a single‐pass transmembrane protein, and it is downregulated in human gastric cancer and levels correlate with tumor progression and time of survival. However, the mechanism of its dysregulation in gastric cancer is little known. Here we investigate its regulatory mechanism and the bidirectional regulation between TMEFF2 and STAT3 in gastric carcinogenesis. TMEFF2 expression was decreased after Helicobacter pylori (H. pylori) infection in vivo and in vitro. STAT3 directly binds to the promoter of TMEFF2 and regulates H. pylori‐induced TMEFF2 downregulation in normal gastric GES‐1 cells and gastric cancer AGS cells. Conversely, TMEFF2 may suppress the phosphorylation of STAT3 and TMEFF2‐induced downregulation of STAT3 phosphorylation may depend on SHP‐1. A highly inverse correlation between the expression of TMEFF2 and pSTAT3 was also revealed in gastric tissues. We now show the deregulation mechanism of TMEFF2 in gastric carcinogenesis and identify TMEFF2 as a new target gene of STAT3. The phosphorylation of STAT3 may be negatively regulated by TMEFF2, and the bidirectional regulation between TMEFF2 and STAT3 may contribute to H. pylori‐associated gastric carcinogenesis.© 2014 UICC